2018
DOI: 10.1002/hed.25341
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in the choice of definitive treatment for squamous cell carcinoma of the oral cavity

Abstract: The non-Hispanic black patients are less likely to receive or be recommended surgery for oral cavity SCC and are more likely to refuse surgery. Further study is needed to identify strategies to close this disparity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
1
19
0
1
Order By: Relevance
“…Racial disparities are well documented across multiple types of cancers, including head and neck squamous cell carcinoma (HNSCC) 1–4 . Black patients with HNSCC face worse prognoses, are less likely to receive the standard of care therapy, and have worse overall survival 4–11 . Some of the differences may be explained by comorbid conditions, differences in stage at presentation, socioeconomic status, and hospital factors 3,4,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Racial disparities are well documented across multiple types of cancers, including head and neck squamous cell carcinoma (HNSCC) 1–4 . Black patients with HNSCC face worse prognoses, are less likely to receive the standard of care therapy, and have worse overall survival 4–11 . Some of the differences may be explained by comorbid conditions, differences in stage at presentation, socioeconomic status, and hospital factors 3,4,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Harmful outcomes from racial disparities have been extensively researched in the US, with one 2019 OMFS study investigating the patient's choice of treatment for oral squamous cell carcinoma between different ethnicities. 5 The study found that, despite statistically significantly better outcomes with surgery rather than chemoradiotherapy, the Black patients were significantly less likely than the white patients to receive surgery. 5 Further to this, a blinded retrospective analysis to determine the independent effect of ethnicity on analgesic prescriptions in A&E found that Black patients received less analgesia than white patients.…”
Section: Bias Within Dentistrymentioning
confidence: 94%
“…5 The study found that, despite statistically significantly better outcomes with surgery rather than chemoradiotherapy, the Black patients were significantly less likely than the white patients to receive surgery. 5 Further to this, a blinded retrospective analysis to determine the independent effect of ethnicity on analgesic prescriptions in A&E found that Black patients received less analgesia than white patients. 58 Although they had the same fractures and reported similar pain levels, 66% more Black patients than white received no analgesia.…”
Section: Bias Within Dentistrymentioning
confidence: 94%
See 2 more Smart Citations